The prevalence of mental health disorders and symptoms in children and adolescents with cerebral palsy: a systematic review and meta‐analysis. (15th September 2017) - Downs, Jenny; Blackmore, Amanda Marie; Epstein, Amy; Skoss, Rachel; Langdon, Katherine; Jacoby, Peter; Whitehouse, Andrew J O; Leonard, Helen; Rowe, Peter W; Glasson, Emma J; ,
Abstract : Aim: Mental health conditions and problems are often reported in children and adolescents with cerebral palsy (CP). A systematic review was undertaken to describe their prevalence. Method: MEDLINE and PsycINFO databases from 1996 to 2016 were searched and reference lists of selected studies were reviewed. Studies were included if they reported point prevalence of mental health diagnoses or symptoms in a general population of children and/or adolescents with CP. Pooled prevalence for mental health symptoms was determined using a random effects meta‐analysis. Results: Of the 3158 studies identified, eight met the inclusion criteria. Mental health disorders were diagnosed by psychiatric interview in one study, giving a prevalence of 57% (32 out of 56 children). The remaining seven studies ( n =1715 children) used parent‐report mental health screening tools. The pooled prevalence for mental health symptoms using the Strengths and Difficulties Questionnaire ( n =5 studies) was 35% (95% confidence interval [CI] 20–61) and using the Child Behavior Checklist ( n =2 studies) was 28% (95% CI 22–36). Evidence was characterized by a moderate level of bias. Interpretation: More studies are needed to ascertain the prevalence of mental health disorders. Mental health symptoms are common and mental health evaluations should be incorporated into multidisciplinary assessments for these children. What this paper adds: Children with cerebral palsy and intellectual disability have a higher risk of mental health symptoms. The prevalence of mental health symptoms for age and severity groups is unclear. What this paper adds: Children with cerebral palsy and intellectual disability have a higher risk of mental health symptoms. The prevalence of mental health symptoms for age and severity groups is unclear. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.